Carbon Nanotube-Titanium Composites-based Antennas for 6G Wireless Networks: Performance Evaluation - Jafaar Fahad A. Rida; Basim Abood (Decision Making: Applications in Management and Engineering, 2025)
The development of innovative communication systems employing carbon nanotube–titanium (CNT–Ti) composite-based antennas remains a challenging task, particularly with regard to optimising their performance. Consequently, the design phase assumes a critical role in advancing these antennas. In this context, the performance of CNT–Ti composite antennas was assessed for their potential application in future 6G wireless communication networks. These antennas exhibited notable characteristics, including high efficiency, wide bandwidth, considerable flexibility, and improved impedance features, rendering them well-suited for 6G networks and high-speed data transmission. Furthermore, the analysis of CNT–Ti composite antennas revealed superior properties relative to conventional antennas, such as enhanced electrical conductivity, low loss tangent, minimal energy dissipation, high signal efficacy, broad bandwidth, and reduced voltage standing wave ratio (VSWR). Although antennas with specialised directional patterns, such as those used in satellite communications, may face constraints in widespread application due to their large size and high manufacturing costs, the study emphasised that further research should focus on optimising the production processes, cost-efficiency, design scalability, and long-term reliability of these antennas. Such investigations would facilitate their sustainable integration into large-scale wireless network technologies.